PENINGKATAN KUALITAS PUPUK ORGANIK PRODUKSI KELOMPOK TANI RUKUN SEJAHTERA DI DESA BUALO KECAMATAN PAGUYAMAN KABUPATEN BOALEMO PROVINSI GORONTALO - Baderan, Nurdin; Moonti, Agustinus; Taha, Siswatiana Rahim; Jamin, Fitriah Suryani; Rahman, Rival (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2021)
Provision of organic fertilizers was done as an alternative to reduce dependence on inorganic fertilizers, even though they were substantive in nature. Apart from being one of the solutions to the scarcity of subsidized fertilizers, it was also an effort to increase agricultural production, as well as protect the plant environment from pollution and maintain soil fertility. The production of organic fertilizers from local agricultural waste has been proven and successfully carried out by farmer groups based on visual criteria that are fine-textured, black in color and smell of soil. Testing of the nutritional content of organic fertilizers has been carried out and the results prove that the minimum technical requirements for solid organic fertilizers have been met, so that larger scale production can be carried out by farmer groups. To follow up on this activity, suggestions that need to be made include: (a) the potential for agricultural waste from sugarcane and oil palm plantations that has not been used in the manufacture of organic fertilizers can be used as raw material, so that it will enrich the nutritional content and the novelty of this organic fertilizer; (b) the need for licensing for the production of organic fertilizer for farmer groups requires assistance from the instant dan associated with these authority dan regulation; and (c) the need for good and attractive packaging, so that it will market-oriented. Key words: Quality, organic fertilizer, local raw materials.